2017
DOI: 10.1051/0004-6361/201731432
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and modelling of white dwarfs with extremely weak magnetic fields

Abstract: Magnetic fields are detected in a few percent of white dwarfs. The number of such magnetic white dwarfs known is now some hundreds. Fields range in strength from a few kG to several hundred MG. Almost all the known magnetic white dwarfs have a mean field modulus ≥ 1 MG. We are trying to fill a major gap in observational knowledge at the low field limit (≤ 200 kG) using circular spectro-polarimetry. In this paper we report the discovery and monitoring of strong, periodic magnetic variability in two previously d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…WD1953-011 Maxted et al, 2000) MWDs. Furthermore, there are examples of both high field (Euchner et al, 2005), and low field (Maxted et al, 2000;Landstreet et al, 2017) MWDs that appear to exhibit a similar level of field complexity. The complexity of the field could be linked to its origin.…”
Section: Complexity Of Field Structure Field Decay and Field Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…WD1953-011 Maxted et al, 2000) MWDs. Furthermore, there are examples of both high field (Euchner et al, 2005), and low field (Maxted et al, 2000;Landstreet et al, 2017) MWDs that appear to exhibit a similar level of field complexity. The complexity of the field could be linked to its origin.…”
Section: Complexity Of Field Structure Field Decay and Field Evolutionmentioning
confidence: 99%
“…It has been known for some time that MWDs tend to exhibit complex field structures and that off-centred dipole models generally produce a better fit to spectroscopic observations than centred dipole models (see Wickramasinghe and Ferrario, 2000). Structures with dominant quadrupolar components or evidence for signif-3 icant contributions from higher order multipoles have also emerged from detailed modelling of isolated and accreting MWDs (Maxted et al, 2000;Euchner et al, 2005Euchner et al, , 2006Beuermann et al, 2007;Landstreet et al, 2017), although not all MWDs require complex field structures to understand their spectra. This suggests that there may be a complex interplay between fossil and dynamo generated fields during stellar evolution and/or stellar merging events which are still poorly understood phenomena despite some extensive studies conducted over many decades (Tout et al, 2004;Brun et al, 2005;Featherstone et al, 2009;Potter and Tout, 2010;Quentin and Tout, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The hot hydrogen-rich white dwarf EUVE J0317-85.5 also appears to have an underlying field of ∼ 185 MG with a high field spot of ∼ 425 MG (Vennes et al 2003). More recently, Landstreet et al (2017) reported on the field topology of two magnetic white dwarfs with fields less than 200 kG, with one star (WD 2047+372) having a field topology corresponding to a simple dipole and the other (WD 2359−434) having a more complex topology with an underlying dipolar field and an overlaying quadrupolar field.…”
Section: Introductionmentioning
confidence: 99%
“…In part this difference between WD 1105-340 and WD 2150+591 may be due to the much stronger field present on WD 2150+591, which leads to significant variation in the wavelengths of the σ components due to even moderate variations in the local value of |B|. However, this difference between the two stars in the width of the σ components relative to the π component is similar to the difference noted between WD 2047+372 (with |B| = 60 kG and very well-defined σ components) and WD 2359-434 (with |B| ∼ 50 − 100 kG and very diffuse σ components) (Landstreet et al 2017). For that pair of stars, the different appearance of the σ components was apparently a symptom of rather different global magnetic field structures, with that of the young star WD 2047+372 being "simpler" than that of the considerably older WD 2359-434.…”
Section: Preliminary Modelling Of Field Structurementioning
confidence: 68%